Experimento com painel fotovoltaico para avaliação do potencial solar no município de Assu-RN - Dantas, Mayke Israel Araújo (Universidade Federal Rural do Semi-Árido, 2019)
With the so-called oil crisis in 1970, it started the technological race for find fonts of alternative energies to decrease the great dependence that existed of fossil fuels, who were responsible by practically all global energy matrix of the time. With this search being escorted by technology several renewable energy sources but one in particular caught the eye the academic community and large investors of the energy sector, the solar energy that is used for heating and also for electricity generation was an area that received a lot of investment in recent years. This paper intends to present basic concepts about photovoltaic technology, as well as its history, and using a solar panel with capacity of 10 W of power, Collect electric power data, voltage and electric current, in order to estimate an apparent solar potential In the city of Assu-RN. It was verified that the number of days of data collection was insufficient to be totally certain of the solar potential in the city of Assu-RN.
Monografia
Keywords: Energia solar; Painel Fotovoltaico; Temperatura; Potencial solar; Wind energy; Photovoltaic panel; Temperature; Solar potential; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA